A methodology to determine the seismic low-cycle fatigue strength of timber connections. (20th January 2020) - Casagrande, Daniele; Bezzi, Stefano; D'Arenzo, Giuseppe; Schwendner, Sascha; Polastri, Andrea; Seim, Werner; Piazza, Maurizio
Highlights: The seismic low-cycle fatigue strength of timber connections is investigated. A relationship between the impairment of strength and slip amplitude is defined. The strength degradation is considered for the determination of ultimate slip. A classification based on the seismic low-cycle fatigue strength is proposed. Abstract: In this paper the seismic low-cyclic fatigue strength for different typologies of dissipative timber connections is analysed by means of a novel methodology, which defines an interaction between the strength degradation and the ductility capacity. The results of more than 40 cyclic tests on panel-to-timber, timber-to-timber, steel-to-timber connections and mechanical anchors are reported and discussed, by defining an approximated linear relationship between the slip amplitude and the impairment of strength from the 1st to 3rd cycle. A proposal for considering the strength degradation as an additional condition in the determination of ultimate slip of dissipative connections subjected to low-cyclic load testing is presented. The seismic low-cycle fatigue strength in terms of ductility capacity and strength degradation is compared for all the tested connection. Four different categories of connections in terms of low-cycle fatigue strength are proposed.